Production of Flavorant and Colorant from Pacific White Shrimp (Litopenaeus vanamei) Head and Their Food Applications - Sineenath Sukkwai (Prince of Songkla University, 2019)
Thesis (Ph.D., Food Science and Technology)--Prince of Songkla University, 2017